Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, Bettina; Elser, Dominique Alexander; Bartley, Tim; Sabuncu, Metin; Wittmann, Christoffer; Sych, Denis; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2010)
We investigate the properties of an atmospheric channel for free space quantum communication with continuous polarization variables. In our prepare-and-measure setup, coherent polarization states are transmitted through an atmospheric quantum channel of 100 m length on the flat roof of our institute's building. The signal states are measured by homodyne detection with the help of a local oscillator (LO) which propagates in the same spatial mode as the signal, orthogonally polarized to it. Thus the interference of signal and LO is excellent and atmospheric fluctuations are auto-compensated. The LO also acts as a spatial and spectral filter, which allows for unrestrained daylight operation. Important characteristics for our system are atmospheric channel influences that could cause polarization, intensity and position excess noise. Therefore we study these influences in detail. Our results indicate that the channel is suitable for our quantum communication system in most weather condition
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.optik.1optik.atmosp

Depolarized guided acoustic wave Brillouin scattering in hollow-core photonic crystal fibers - Zhong, Wenjia; Stiller, Birgit; Elser, Dominique Alexander; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2015)
By performing quantum-noise-limited optical heterodyne detection, we observe polarization noise in light after propagation through a hollow-core photonic crystal fiber (PCF). We compare the noise spectrum to the one of a standard fiber and find an increase of noise even though the light is mainly transmitted in air in a hollow-core PCF. Combined with our simulation of the acoustic vibrational modes in the hollow-core PCF, we are offering an explanation for the polarization noise with a variation of guided acoustic wave Brillouin scattering (GAWBS). Here, instead of modulating the strain in the fiber core as in a solid core fiber, the acoustic vibrations in hollow-core PCF influence the effective refractive index by modulating the geometry of the photonic crystal structure. This induces polarization noise in the light guided by the photonic crystal structure.
CRIS-Team Scopus Importer:2021-06-29

Enhanced free space beam capture by improved optical tapers - Bartley, Tim; Heim, Bettina; Elser, Dominique Alexander; Sych, Denis; Sabuncu, Metin; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (2010)
In our continuous variable quantum key distribution (QKD) scheme, the homodyne detection set-up requires balancing the intensity of an incident beam between two photodiodes. Realistic lens systems are insufficient to provide a spatially stable focus in the presence of large spatial beam-jitter caused by atmospheric transmission. We therefore present an improved geometry for optical tapers which offer up to four times the angular tolerance of a lens. The effective area of a photodiode can thus be increased, without decreasing its bandwidth. This makes them suitable for use in our free space QKD experiment and in free space optical communication in general. © Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering 201
Keywords: Atmospheric optics; Beam-jitter; Free space communication; Optical taper; Quantum key distribution; Random media

Feasibility of free space quantum key distribution with coherent polarization states - Heim, Bettina; Leuchs, Gerd; et al. (New Journal of Physics, 2009)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.feasib

Proof-of-principle test of coherent-state continuous variable quantum key distribution through turbulent atmosphere - Derkach, Ivan; Peuntinger, Christian; Ruppert, Laszlo; Heim, Bettina; Gunthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd (SPIE Security + Defence, 2016)
Continuous-variable quantum key distribution is a practical application of quantum information theory that is aimed at generation of secret cryptographic key between two remote trusted parties and that uses multi-photon quantum states as carriers of key bits. Remote parties share the secret key via a quantum channel, that presumably is under control of of an eavesdropper, and which properties must be taken into account in the security analysis. Well-studied fiber-optical quantum channels commonly possess stable transmittance and low noise levels, while free-space channels represent a simpler, less demanding and more flexible alternative, but suffer from atmospheric effects such as turbulence that in particular causes a non-uniform transmittance distribution referred to as fading. Nonetheless free-space channels, providing an unobstructed line-of-sight, are more apt for short, mid-range and potentially long-range (using satellites) communication and will play an important role in the future development and implementation of QKD networks. It was previously theoretically shown that coherent-state CV QKD should be in principle possible to implement over a free-space fading channel, but strong transmittance fluctuations result in the significant modulation-dependent channel excess noise. In this regime the post-selection of highly transmitting sub-channels may be needed, which can even restore the security of the protocol in the strongly turbulent channels. We now report the first proof-of-principle experimental test of coherent state CV QKD protocol using different levels Gaussian modulation over a mid-range (1.6-kilometer long) free-space atmospheric quantum channel. The transmittance of the link was characterized using intensity measurements for the reference but channel estimation using the modulated coherent states was also studied. We consider security against Gaussian collective attacks, that were shown to be optimal against CV QKD protocols . We assumed a general entangling cloner collective attack (modeled using data obtained from the state measurement results on both trusted sides of the protocol), that allows to purify the noise added in the quantum channel . Our security analysis of coherent-state protocol also took into account the effect of imperfect channel estimation, limited post-processing efficiency and finite data ensemble size on the performance of the protocol. In this regime we observe the positive key rate even without the need of applying post-selection. We show the positive improvement of the key rate with increase of the modulation variance, still remaining low enough to tolerate the transmittance fluctuations. The obtained results show that coherent-state CV QKD protocol that uses real free-space atmospheric channel can withstand negative influence of transmittance fluctuations, limited post-processing efficiency, imperfect channel estimation and other finite-size effects, and be successfully implemented. Our result paves the way to the full-scale implementation of the CV QKD in real free-space channels at mid-range distances.<br